Impaired endothelial function in siblings of patients with diabetic mellitus type 2. Issue 1 (December 2015) - Rasmi, Yousef; Emamy-Nagadeh, Kani; Valizadeh, Neda; Saleh-Mogadam, Masoud; Shirpoor, Alireza; Saboory, Ehsan
Abstract Background Endothelial dysfunction is considered as a risk factor for cardiovascular disease, which is a consistent finding in diabetic mellitus type 2 (DMT2). First-degree relatives of DMT2 patients have a higher risk of developing DMT2 later on the life. We aimed to investigate whether impaired endothelial function exists in siblings of DMT2 patients. Methods As endothelial function markers, plasma E-selectin, soluble inter-cellular adhesion molecule-1 (sICAM-1), and endothelin-1 (ET-1) were measured on 27 DMT2 patients (9 m/18f; mean age: 48.48 ± 6.75 years), 28 siblings of DMT2 patients (14 m/14f; mean age: 44.54 ± 7.10 years), and 30 control subjects (18 m/12f; mean age: 44.72± 7.56 years) without any family history of diabetes. All the groups were matched by gender, age, and body mass index (BMI). Results Plasma levels of ET-1, sICAM-1, and E-selectin were significantly higher in the DMT2 group compared to the control group (ET-1:0.79 ± 1.63 pg/ml vs. 0.33 ± 0.08 pg/ml; PCD  = 0.049, sICAM-1: 71.15 ± 27.20 ng/ml vs. 34.57 ± 22.56 ng/ml; PCD  = 0.001, E-selectin: 22.45 ± 11.57 ng/ml vs. 16.28 ± 7.50 ng/ml; PCD =0.026). There was a significant difference in sICAM-1 levels between siblings (62.08 ± 26.37 ng/ml) and controls (PCS  = 0.002), but not between siblings and DMT2 patients (PSD  = 0.411). Moreover, a significant difference was observed in ET-1 levels between siblings (0.75 ± 1.26 pg/ml) and controls (PCS  = 0.031), but not between siblings and DMT2 patients (PSD  = 0.751). There was also a significant difference in E-selectin levels between DMT2 patients and siblings (16.56 ± 8.71 ng/ml; PSD =0.028); however, the difference in E-selectin levels was not statistically significant between siblings and controls (PCS  = 0.919). Conclusion Endothelial function markers in the siblings of DMT2 patients are increased in comparision to the control group Therefore; family history in the DMT2 patients seems to be a risk factor for endothelial function. Furthermore, endothelial dysfunction is available very early in the DMT2 patients, even before overt hyperglycemia ensues (in siblings), and may play a key role in the etiopathology of the vasculopathy associated with DMT2.